1998
DOI: 10.1161/01.atv.18.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Is Associated With an Increased Risk of Cardiovascular Disease, Especially in Non–Insulin-Dependent Diabetes Mellitus

Abstract: Abstract-A high serum total homocysteine (tHcy) level is an independent risk factor for cardiovascular disease. Because it is not known whether the strength of the association between hyperhomocysteinemia and cardiovascular disease is similar for peripheral arterial, coronary artery, and cerebrovascular disease, we compared the three separate risk estimates in an age-, sex-, and glucose tolerance-stratified random sample (nϭ631) from a 50-to 75-year-old general white population. Furthermore, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
209
5
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(229 citation statements)
references
References 34 publications
9
209
5
2
Order By: Relevance
“…39,40 Several studies also showed a significant association between Hcy and BP, [4][5][6][41][42][43][44][45] or HTN; 1,46 however, no association was found in other studies 47,48 (Table 6). Recently, a randomized, placebo-controlled, Hcy-lowering trial reported a decrease in BP in response to treatment.…”
Section: Discussionmentioning
confidence: 97%
“…39,40 Several studies also showed a significant association between Hcy and BP, [4][5][6][41][42][43][44][45] or HTN; 1,46 however, no association was found in other studies 47,48 (Table 6). Recently, a randomized, placebo-controlled, Hcy-lowering trial reported a decrease in BP in response to treatment.…”
Section: Discussionmentioning
confidence: 97%
“…These interactions were further strengthened when postmethionine-load homocysteine levels were taken into account. Moreover, the hyperhomocysteinemia associated with an increased cardiovascular risk is stronger in non-insulin-dependent diabetes mellitus than in normal subjects (Hoogeveen et al, 1998). Thus, there are pronounced interactive effects with classic risk factors, suggesting that homocysteine might further increase the cardiovascular risk in patients bearing these risk factors.…”
Section: Interactions Between Hyperhomocysteinemia and The Usual Riskmentioning
confidence: 99%
“…Even though elevated homocysteine levels contribute to the development of atherosclerosis independently of classical cardiovascular risk factors in diabetic subjects [25,26], the relationship between Hcy and diabetes is still debated. Plasma homocysteine levels have been reported to be normal, reduced or elevated in patients with diabetes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%